A Change of Mind: Applying Social and Behavioral Research Methods to the Assessment of the Effectiveness of Ocean Literacy Initiatives - Ashley, Matthew; Pahl, Sabine; Glegg, Gillian; Fletcher, Stephen (Frontiers in Marine Science, 2019)
Assessment of environmental literacy and ocean literacy focus on increasing knowledge and awareness. The goal of ocean literacy initiatives is ultimately to enable behaviour change (whereby citizens take direct and sustainable action) to achieve sustainable solutions to marine environment issues. The application of social and behavioural research methods provides powerful tools for assessing if ocean literacy initiatives are effective at increasing participant’s knowledge and awareness of an issue, its causes and consequences and behaviours or actions required to enable sustainable solutions. Social and behavioural research methods also provide a means of assessing changes in attitude, a key predictor of behaviour change, and ultimately a means of assessing changes in a participants intended and reported behaviours. We present a framework to integrate social and behavioural research methods within assessment of the effectiveness of ocean literacy initiatives. The before and after assessment we undertake develops existing environmental literacy and ocean literacy assessment approaches by integrating social and behavioural research methods to assess key predictors of behaviour change. We structured the assessment methodology within a Theory of Change logic model, to provide a protocol for systematic evaluation of ocean literacy initiatives and tools. Specifically those aimed at promoting specific behaviour change objectives for pre-identified actors. Assessment of educational training courses for professionals entering the shipping industry (targeting behaviours to reduce the spread of invasive species), and educational workshops for school students (aged 11-15 and 16-18), on problems related to marine litter and microplastics and potential solutions were assessed using the framework. Through before and after surveys, an increase in awareness, knowledge and an increase in attitudes supporting action to reduce impacts on the marine environment were reported by participants, after interaction with sets of tools developed by the Horizon 2020 Ocean Literacy project ResponSEAble. Results supported the importance of targeting specific audiences with tailored ocean literacy tools and the importance of informing actors of issues and solutions within the context of wider ocean literacy principles.